2015
DOI: 10.1515/orga-2015-0002
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Social Networking Sites on Recruiting Human Resources in the Czech Republic

Abstract: Background: This paper is focused on the usage of social networking sites (SNS) for human resources departments in the process of hiring new employees. It also maps the development and influence of SNS on recruiter's behavior and customs. The main aim is to find out, whether SNS could/will replace traditional online job boards in the Czech Republic. The motivation for the research is to determine whether SNS can be used for serious and practical business purposes. Methods: The paper presents authors' empirical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The unwillingness or inability to use social networking sites for recruitment confirms also Kietzmann et al (2011). On the other hand, Böhmová and Pavlíček (2015) reported that HR specialists use information from public Facebook profiles regularly, and Madera (2012) and Chauhan, Buckley, and Har et al (2013) write about the growing trend of using social networks for active recruitment. Lewis et al (2015) claim that LinkedIn is recruiters' most popular social media, 60% of surveyed companies claimed successful intake of the new employee through social media such as Facebook, Twitter, or LinkedIn.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The unwillingness or inability to use social networking sites for recruitment confirms also Kietzmann et al (2011). On the other hand, Böhmová and Pavlíček (2015) reported that HR specialists use information from public Facebook profiles regularly, and Madera (2012) and Chauhan, Buckley, and Har et al (2013) write about the growing trend of using social networks for active recruitment. Lewis et al (2015) claim that LinkedIn is recruiters' most popular social media, 60% of surveyed companies claimed successful intake of the new employee through social media such as Facebook, Twitter, or LinkedIn.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The data about candidates from social media networks is significantly important for organizations. (Böhmová, Mcloughlin & Střížová, 2016) Therefore, the following section describes how data can be extracted. Most of the social media networks offer two different options to integrate own applications.…”
Section: Data Extraction From Social Media Networkmentioning
confidence: 99%